Induced sputum in children: feasibility, repeatability, and relation of findings to asthma severity. Issue 9 (1st September 2000) - Wilson, Nicola M; Bridge, Peter; Spanevello, Antonio; Silverman, Michael
Abstract : BACKGROUND: The collection of induced sputum provides a non-invasive method of investigating airway inflammation. Few studies have been performed in children, so a study was undertaken to determine the feasibility of sputum induction, the repeatability of eosinophil counts and sputum eosinophil cationic protein (ECP) levels, and the relation of these to current asthma severity. For comparison, serum ECP levels were also measured. METHODS: In a cross sectional study of children aged 5–15 years, 27 healthy children and 60 with asthma underwent sputum induction using inhaled nebulised hypertonic saline. The whole sputum sample was used for analysis. Ten children with stable asthma repeated the procedure within 10 days. RESULTS: A satisfactory sample (>500 non-squamous cells) was obtained in 61% of children with asthma and in 60% of healthy controls. The limits of agreement within subjects ranged from a 0.68 to 2.8 fold difference for eosinophil differential counts and from 0.38 to 4.4 fold for sputum ECP. Despite a median of 42% squamous cells, significant differences were found between asthma and healthy controls for the eosinophil differential count (p = 0.0004), total eosinophil counts (p = 0.03), and sputum ECP level (p = 0.0001). Overall, there was no correlation between any marker of airway inflammation and asthma severity, however expressed, including lung function. CONCLUSIONS: Sputum induction is only possible in a proportion of children. The repeatability of sputum cell counts and ECP levels, measured in a small number of children, was similar to that reported in adults. Sputum analysis revealed no evidence of airway inflammation in a number of highly symptomatic children with asthma.